Frequency and Cost of Diabetic Ketoacidosis in Germany – Study in 12 001 Paediatric Patients - Icks, A.; Strassburger, K.; Baechle, C.; Rosenbauer, J.; Giani, G.; Beyer, P.; Holl, R. W. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Recently, medical expenditures were found to be 2-fold increased in paediatric patients with diabetic ketoacidotic events (DKA) in the U.S., in particular due to hospitalization. Aim of our study was to analyse DKAs and associated costs in Germany, where structured diabetes care including education is available for all patients.For all 12 001 diabetic patients 0–19 years of age (52.6% male, mean age (SD) 12.6 (3.9) years) documented in a German-wide database, all DKAs were assessed, as well as costs for diabetes-related treatment. Associations between costs and DKA were estimated using log-linear models.457 (3.8%) patients had at least 1 DKA during 2007. Total annual costs for patients without, with 1, or ≥ 2 DKAs were € 3 330 (95%-CI 3 292–3 368), € 6 935 (CI 6 627–7 244), and € 10 728 (CI 9 813–11 644), respectively, with largest differences for hospitalization costs (€ 693, € 4 145, € 8 092). Age-sex-diabetes duration-adjusted cost ratios for patients with 1, or ≥ 2 DKAs compared to patients without DKA were 2.2 (CI 2.1–2.3) and 3.6 (CI 3.1–4.1), respectively.In Germany, paediatric diabetic patients with DKA had up to 3.6-fold higher diabetes-related costs compared to those without DKA. This cost excess was higher compared to a U.S. study, however, the proportion of patients with DKA was much lower (3.8% versus 14.9%). The lower frequency of DKA in Germany may be due to a higher access to and utilization of diabetes education. Interventions should reduce DKA and resulting hospital admission in pediatric patients in order to reduce costs and improve quality of life.
Keywords: type 1 paediatric diabetes; diabetic ketoacidosis; costs